Biobriket Berbasis Limbah Lignoselulosa Berstandar Mutu SNI: Review - Mochammad Fajar Aliyyansyah; Cantika Wahyu Maharani; Reni Febriani; Asep Kadarroman (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2025)
The depletion of non-renewable energy reserves encourages the development of alternative renewable energy sources, such as biomass energy. Biomass is an organic material derived from living organisms and contains biochemical compounds such as carbohydrates, proteins, and fats. Moreover, biomass also contains lignocellulose, which holds significant potential as a raw material for energy products such as bio briquettes. This article aims to examine the characteristics of bio briquettes from lignocellulose waste based on SNI briquette quality standards. Data search using literature studies with searches on Google Scholar, Research Gate, and ScienceDirect with the keywords "Lignocellulosic waste", "Biomass", and "Bio briquettes". The selected literature includes journals and national scientific seminar proceedings from the last ten years, screened using the PRISMA diagram. The literature used was 21 journals indexed in SINTA, 5 journals indexed in Scopus, 2 journals indexed in Garuda, 5 non-indexed journals obtained through Google Scholar, and 3 national scientific seminar proceedings, the data obtained was processed using meta-analysis. The results show that the characteristics of bio briquettes are influenced by the raw material. Bio Briquettes that comply with SNI standards can be assessed based on their lignocellulose content. Materials with high lignin levels tend to have a higher calorific value, making them potentially optimal raw materials. In contrast, materials with low lignin content have lower energy potential during combustion. Overall, lignocellulosic waste has significant potential as a raw material for high-quality bio briquettes based on SNI quality standards, especially through production process optimization by combining various raw materials. Keywords: Bio Briquettes, biomass, lignocellulose waste, SNI quality standards